Two-year outcomes after percutaneous coronary intervention with drug-eluting stents or bare-metal stents in elderly patients with coronary artery disease - Lafont, Alexandre; Sinnaeve, Peter R; Cuisset, Thomas; Cook, Stéphane; Sideris, Giorgios; Kedev Sasko; Carrie, Didier; Hovasse, Thomas; Garot, Philippe; El Mahmoud, Rami; Spaulding, Christian; Helft, Gérard; et al. (Wiley, 2020)
Report the results at 2 years of the patients included in the SENIOR trial.